Spatial distribution patterns and influencing factors of China's new energy vehicle industry. (15th December 2022) - Cao, Li; Deng, Feng; Zhuo, Chengfeng; Jiang, Yunyan; Li, Zhengbo; Xu, Huachao
Abstract: New energy vehicles (NEVs) have been recognized as a sustainable eco-innovation to address China's energy and environment problems. As a strategically emerging industry, China's NEV manufacturing industry has been prioritized by governments and manufacturers, significantly impacting its spatial distribution pattern and stimulating the goals of carbon peaking and carbon neutralization. China, the largest NEV producer and consumer and with distinctive regional diversity, has experienced a new round of capacity expansion. Therefore, the literature on the spatial distribution patterns and influencing factors of NEV industry in provincial level is vital for the transformation of manufacturing industry and transportation sector, while to date, the related studies is few. In this paper, considering the number and location of key enterprises/production bases, the spatial distribution and influencing factors of China's NEV industry were discussed by an empirical study. The results are gained from a spatial perspective. Firstly, in general, China's NEV industry presents a "T" spatial distribution pattern. Secondly, a point-axle spatial exploration pattern is proposed, which includes "four points and one axle" namely Bohai rim, Yangtze River Delta (YRD), Pearl River Delta (PRD), Hubei-Chongqing clusters and Eastern Coastal NEV industrial belt. Thirdly, different types of NEV enterprises show various location preferences and spatial distribution characteristics. Fourthly, the influencing factors on China's NEV spatial distribution are concluded from five aspects of supporting policy, infrastructure condition, economic drivers, technical capacity, and industrial foundation, and the degree of factors is different considering varying enterprise classification and industrial development stage. The findings of this paper provide a reference for rational layout in China's NEV industry, and are expected to stimulate the sustainable development of NEVs.